Front Cover: The Insertion of EII and EIV Chlorides (E=Si, Ge) into the Si−Si Bond of Disilylene (Chem. Eur. J. 70/2022). Issue 70 (7th December 2022) - Baradzenka, Aliona G.; Vyboishchikov, Sergei F.; Pilkington, Melanie; Dmitrienko, Anton; Nikonov, Georgii I.
Abstract : Insertion of silylene : SiCl2 into the Si−Si bond of a phosphinoamidinate‐supported disilylene affords a SiCl2 ‐bridged bis(silylene) that, upon heating, rearranges into a silyl‐substituted disilylene. Analogous insertion of GeCl2 leads directly to a silyl‐substituted silylene‐germylene derivative. More information can be found in the Research Article by S. F. Vyboishchikov, G. I. Nikonov and co‐workers (DOI: 10.1002/chem.202202799 ).